Entre tensões e proposições: um estado do conhecimento sobre a aprendizagem histórica no Brasil em dissertações e teses (2005-2018) - Mistura, Letícia (2019)
In this study, a state of knowledge research, we focus analytically on a corpus of 63 doctoral dissertations and master’s thesis, elaborated in stricto sensu Brazilian postgraduate programs, in order to understand the development of the theme of "historical learning", which has been drawn expressively within the field of investigation of History Teaching. The corpus, which contemplates a 13-year period (2005-2018), was delimited by means of searches in the Catálogo de Teses e Dissertações da Capes, using the terms "historical learning", "History Education" and "learning of History ". In the course of corpus analysis, it was examined: a) the theoretical conceptions of “historical learning” that guided the researchers, visualizing it in a theoretical drawing composed of three matrices that dialogued with authors of different fields: from the Philosophy of History (Jörn Rüsen), from English History Education (Peter Lee, Alaric Dickinson, Rosalyn Ashby) and the from the Cognitive Development, Learning and Social Psychology Sciences (Lev Vigotski, Jean Piaget and Serge Moscovici); b) what propositions are made to historical learning; and c) what knowledge has been produced about historical learning in Brazil, through the articulation between the conceptions of learning conceptions, problems and propositions. Thus, an inventory of the Brazilian academic production on “historical learning” and an agenda of future research prospects and challenges were built. The agenda points mainly to the need for reflection on research procedures and instruments, on the assessment of learning, on the possibility of a closer dialogue between historical learning and language and the overcoming of theoretical dichotomies in the studies about historical learning.